Glucose Reduction Prevents Replicative Senescence and Increases Mitochondrial Respiration in Human Mesenchymal Stem Cells - Ting Lo; Jennifer H. Ho; Muh-Hwa Yang; Oscar K. Lee M.D., Ph.D. (Cell Transplantation, 2011)
The unique self-renewal and multilineage differentiation potential of mesenchymal stem cells (MSCs) make them a promising candidate for cell therapy applications. However, during in vitro expansion of MSCs, replicative senescence may occur and will compromise the quality of the expanded cells. Because calorie restriction has been shown to effectively extend the life span of various organisms, the purpose of this study is to investigate the effect of glucose reduction on MSCs and the coordinated changes in energy utilization. It was found that the frequency of cycling cells was significantly increased, while senescence markers such as β-galactosidase activities and p16 INK4a expression level were markedly reduced in MSCs under low-glucose culture condition. Quantitative real-time PCR analysis demonstrated the preserved trilineage differentiation potentials of MSCs after low-glucose treatment. Interestingly, the ability of osteogenic lineage commitment was improved, while the ability of adipogenic lineage commitment was delayed in MSCs after glucose reduction. In addition, we observed decreased lactate production, increased electron transport chain complexes expression, and increased oxygen consumption in MSCs after glucose reduction treatment. Increased antioxidant defensive responses were evidenced by increased antioxidant enzymes expression and decreased superoxide production after glucose reduction. Taken together, our findings suggest that MSCs utilize energy more efficiently under restricted glucose treatment and exhibit greater self-renewal and antisenescence abilities, while their differentiation potentials remain unaffected.